An increase in SNHG5 expression is associated with poor cancer prognosis, according to a meta-analysis - Qiang Huang; Yi-gui Xia; Yong-jian Huang; Hai-feng Qin; Qun-xian Zhang; Chun-feng Wei; Wu-ru Tang; Yuan Liao (European Journal of Medical Research, 2024)
Abstract Background He long noncoding RNA small nucleolar host RNA 5 (SNHG5) is highly expressed in many cancers, and there is a notable correlation between the elevated expression of SNHG5 and survival outcome in cancer patients. The objective of this study was to conduct a meta-analysis to evaluate the correlation between SNHG5 expression and the clinical outcome of cancer patients. Methods Six relevant electronic databases were exhaustively searched, and, depending on the inclusion and exclusion criteria, appropriate literature was obtained. The Newcastle-Ottawa Scale (NOS) score was utilized to evaluate the quality of the research for every article included, and pertinent data from each study were carefully extracted. Hazard ratios (HRs), odds ratios (ORs) and 95% confidence intervals (CIs) were combined to explore the association of SNHG5 expression levels with cancer prognosis, and sensitivity analyses and assessments of publication bias were also conducted to investigate any possibility in the publication of the studies. Results Eleven studies encompassing 721 patients were ultimately collected. When combined, the hazard ratios (HRs) revealed a substantial direct correlation between elevated SNHG5 expression and an unfavourable prognosis for cancer patients (HR = 1.90, 95% CI 0.87–4.15); however, the correlation did not reach statistical significance. Furthermore, high SNHG5 expression was predictive of advanced TNM stage (OR: 1.988, 95% CI 1.205–3.278) and larger tumour size (OR: 1.571, 95% CI 1.090–2.264); moreover, there were nonsignificant relationships between SNHG5 expression and DM (OR: 0.449, 95% CI 0.077–2.630), lymph node metastasis (OR: 1.443, 95% CI 0.709–2.939), histological grade (OR: 2.098, 95% CI 0.910–4.838), depth of invasion (OR: 1.106, 95% CI 0.376–3.248), age (OR: 0.946, 95% CI 0.718–1.247) and sex (OR: 0.762, 95% CI 0.521–1.115). Conclusion SNHG5 expression is typically increased in the majority of tumour tissues. Elevated SNHG5 expression may indicate poor prognosis in cancer patients. Therefore, SNHG5 is a promising potential therapeutic target for tumours and a reliable prognostic biomarker.